2023
DOI: 10.1002/advs.202303516
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Neurovascular Coupling and Increased Functional Connectivity in the Frontal Cortex Predict Age‐Related Cognitive Dysfunction

Peter Mukli,
Camila B. Pinto,
Cameron D. Owens
et al.

Abstract: Impaired cerebrovascular function contributes to the genesis of age‐related cognitive decline. In this study, the hypothesis is tested that impairments in neurovascular coupling (NVC) responses and brain network function predict cognitive dysfunction in older adults. Cerebromicrovascular and working memory function of healthy young (n = 21, 33.2±7.0 years) and aged (n = 30, 75.9±6.9 years) participants are assessed. To determine NVC responses and functional connectivity (FC) during a working memory (n‐back) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 86 publications
0
0
0
Order By: Relevance
“…Such insights are crucial for understanding the mechanistic underpinnings of tES in therapeutic contexts, particularly its role in enhancing neurovascular coupling and cognitive function. Indeed, a hallmark of dementia syndromes is an energy deficit in neurons, leading to synaptic loss and resulting in cognitive decline and behavioral changes [ 76 ]; therefore, an energy boost is necessary [ 77 ], e.g., via facilitating neurovascular [ 78 ] and neurometabolic [ 79 ] coupling rather than solely excitatory tDCS that may increase the energy deficit leading to synaptic loss. Also, Gamma entrainment may positively impact excitation/inhibition imbalances by preventing neurochemical changes linked to Aβ, such as hyperexcitability, and triggering neuroprotective mechanisms [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such insights are crucial for understanding the mechanistic underpinnings of tES in therapeutic contexts, particularly its role in enhancing neurovascular coupling and cognitive function. Indeed, a hallmark of dementia syndromes is an energy deficit in neurons, leading to synaptic loss and resulting in cognitive decline and behavioral changes [ 76 ]; therefore, an energy boost is necessary [ 77 ], e.g., via facilitating neurovascular [ 78 ] and neurometabolic [ 79 ] coupling rather than solely excitatory tDCS that may increase the energy deficit leading to synaptic loss. Also, Gamma entrainment may positively impact excitation/inhibition imbalances by preventing neurochemical changes linked to Aβ, such as hyperexcitability, and triggering neuroprotective mechanisms [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to acknowledge that cerebrovascular dysfunction plays a role in the development of age-related cognitive decline. Some studies have shown deficits in neurovascular coupling [114,115], while frontal networks exhibit stronger local and global connectivity. This may suggest that in the elderly, stronger functional connections are needed to compensate for the weakened neurovascular coupling during the performance of a higher demanding task [115].…”
Section: Behavioral and Neuropsychological Assessment In Pbm Studies ...mentioning
confidence: 99%